Islamic Law and Employee Marriage Restrictions : A Case Study of Bank BRI Parepare - Mukarramah Mukarramah; Hasmia Wahyunisa; Ibnu Azka; Fathur Baldan Haramain (SHAHIH: Journal of Islamicate Multidisciplinary, 2025)
This study analyzes the employment policy prohibiting marriage during the contract period from an Islamic legal perspective, using a case study at the BRI Branch Office in Parepare. The policy, institutionally justified as a mechanism to ensure employee focus, discipline, and productivity, creates normative and ethical tensions for Muslim employees for whom marriage is a religious obligation and an integral aspect of moral life in Islam. This research uses qualitative method, collecting data through in-depth interviews with contract employees, human resource managers, and Islamic legal experts, complemented by document analysis of Islamic legal literature, fatwas, and relevant employment regulations. The data are analyzed through thematic and normative analysis. The findings indicate that the marriage prohibition policy lacks a strong justification for maslahah (public benefit) and is inconsistent with core Islamic legal principles, particularly the protection of religion (ḥifẓ al-dīn) and human dignity (karāmah al-insān). Rather than improving performance, such policies can actually cause psychological stress, moral conflict, and spiritual discomfort among employees, potentially damaging long-term productivity. This study contributes to the discourse on Islamic labor law by highlighting the limitations of contractual restrictions when they conflict with fundamental religious rights.